Becoming strong women : physicality, femininity and the pursuit of power : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Sociology at Massey University, Palmerston North, Aotearoa New Zealand - Bell, Martha Guinn (Massey University, 2002)
Women outdoor leaders are often told that they are too aggressive and strident and that they risk being too strong to be role models for their students. They experience competition, hostility, misogynist epithets and sexual advances, as well as coercion to prove themselves from their male students and colleagues. Many of these women report self-doubt and low confidence about their competence and that they do not advance in their careers because they take time to perfect their physical skills. Cultural feminist analyses recommend that activities for women ought not to require intense physical strength and women outdoor leaders should not be so competent that ordinary women cannot aspire to be like them. Prescriptions for all-women groups encourage non-competitive learning experiences which enhance the development of women's inner strengths and protect their psychological safety in the outdoors. Non-separatist remedies agree that women-only courses ensure women are not intimidated by men's physical superiority and argue that they should prepare women to re-enter mixed outdoor programmes with more confidence. These suggestions, however, do not account for the relations of the physical through which women and men socially and subjectively embody physicality. This project takes up corporeal feminism in order to examine in a group of women outdoor leaders their lived experiences of physicality and embodied identity and how these effect often contradictory gendered subjectivities. It responds to the literature by arguing that heterogendered norms are sustained when the performance of prowess is rejected as the 'male model.' In contrast, I argue that women in this study who embrace the 'hard, physical' as masculinity are allowing a non-normative bodily strength to reinscribe their feminine subjectivities. Other women who desire an "acceptable" femininity, whether "big and boisterous" or "staunch," are expanding the possibilities for gendered subjectivity. Strong women know what their bodies can do and often enthusiastically want others to experience this. Their physical prowess makes visible the social conditions through which normative femininity is inscribed as limited physical strength. When they reinscribe femininity with a lived power of strength, endurance and bodily control, they become more effective at challenging gender heteronormativity through alternative physicalities.
Keywords: Self-esteem in women; Body image in women; Recreation leadership; Outdoor recreation for women; Sexism; Feminism; New Zealand; Women leaders; Outdoor leaders; Femininity